Pengaruh Pemasaran Syariah Media Sosial, Kualitas Produk, Harga, dan Review Pelanggan Online Terhadap Keputusan Pembelian Produk Erigo - Sri Walyoto; Sintha Sujarwanti (ITB AAS INDONESIA Surakarta, 2022)
This study aims to analyze the effect of social media promotion, product quality, price, and online customer reviews on purchasing decisions of Erigo products to consumers of Erigo Official Shop Shopee.co.id in Sragen Regency. This research is a type of quantitative research with a questionnaire as data collection material. Samples were taken as many as 100 respondents. The sampling technique used is proportional sampling with non-probability sampling method. While the data analysis technique used instrument test, classical assumption test, model determination test, multiple linear regression analysis and t test processed with the help of IBM SPSS statistics 22 Software. From the results of this study, it can be concluded that partially (t test) shows that the social media promotion variable has a positive and significant effect on purchasing decisions. Product quality variable has a positive and significant effect on purchasing decisions. The price variable has a positive and significant effect on on purchasing decision. Then the online customer review variable has a positive and significant effect on purchasing decisions. It can be suggested that the company continues to strengthen its marketing activities through social media promotion. Furthermore, the pricing strategy can be done by providing discount offers and paying attention to competitors' offers. but the quality of the product must also be considered so that consumers remain confident in their choice. Online customer reviews are an influential factor in the purchasing decision process. Therefore, companies need to pay attention to the content of information about a product from consumers in order to convince potential consumers to buy.